Analysis of Cadet Parent Satisfaction in Educational Services at Politeknik Pelayaran Surabaya - Beno, Jose; Dwi Santoso, Agus; Harianto, Bambang Bagus (Technium Social Sciences Journal, 2023)
The purpose of this research was to determine the level of satisfaction of Taruna parents with educational services at the Surabaya Shipping Polytechnic. There are five aspects of education services, namely Tangibility (physical evidence), reliability (reliability), responsiveness (responsiveness), assurance (assurance), empathy (empathy). This research is descriptive research with a quantitative approach. The subjects of the study were parents of cadets of the Surabaya Cruise Polytechnic. With a sample of 200 parents of cadets Data collection techniques using questionnaires, documents and interviews. Based on the results of the study, it canbe found that high satisfaction is 14%, quite satisfied by 74.5% and dissatisfied by 11.5%, judging from the pie diagram, it is produced that the highest dimensional value is felt to be in the Tangibles dimension or physical evidence such as buildings and facilities and infrastructure, followed by the responsiveness or service dimension to the speed of service and then the assurance dimension, followed by the emphaty dimension and the last one is the reliability dimension. The results of this study have provided positive information related to the satisfaction of Taruna parents with educational services at the Surabaya Cruise Polytechnic. Therefore, it is advisable to evaluate and continuously improve services on all dimensions of educational services within the Surabaya shipping polytechnic in order to improve educational services according to the expectations of parents and the community.